Forensic applications of the MMPI-2 - Ben-Porath, Yossef S. (Applied psychology (Thousand Oaks, Ventura County, Calif.), 1995)
Eleven articles examine issues concerning both research and practice on this most widely used psychological test in forensic psychology, from the scientific bases of forensic applications of the MMPI-2 to its use in the assessment of criminal responsibility. Annotation copyright Book News, Inc. Portland Or.